Research progress on the role of bilirubin in inflammatory bowel disease - SHI Li, YUAN Hao, LIU Min, ZHENG Ya, WANG Yu-ping, GUO Qing-hong (Jichu yixue yu linchuang, 2022)
The role of bilirubin in inflammatory bowel disease is not only functioned as an antioxidant and anti-inflammatory factor, but also functioned in immune regulation, anti-platelet aggregation, and as inhibition factor of digestive protease and remodeling of microbiota. Serum bilirubin level is correlated with disease activity and severity, so is a potential serum marker of inflammatory bowel disease in terms of supporting clinical diagnosis and treatment of inflammatory bowel disease.